Challenges of Diagnosing Severe Ehrlichiosis in Orthotopic Liver Transplant Recipients. (17th November 2021) - Parkinson, Melissa; Vuyyuru, Spandana; Patel, Jay; Animalu, Chinelo
Abstract : In recent solid organ transplant recipients, acute febrile illness is usually a source of grave concern and a diagnostic dilemma, especially if no response is noted after initiation of broad antimicrobial therapy. Human Monocytic Ehrlichiosis (HME) is a tick-borne illness caused by Ehrlichia chaffeensis and is not considered an opportunistic infection in immunocompromised patients such as solid organ transplant patients. Ehrlichiosis in immunocompromised patients can be life-threatening, and a strong index of suspicion is needed, especially in patients who live in endemic areas, for proper treatment initiation with doxycycline. We report a case of a 40-year-old male who received an orthotopic liver transplant six months earlier secondary to primary sclerosing cholangitis, on chronic immunosuppressive medication, who presented with complaints of sudden onset fever associated with nausea, vomiting, and diarrhea. Initial extensive infectious workup was negative and no response to empiric antimicrobials. There was suspicion for ehrlichiosis prompting empiric doxycycline use. Subsequently, E. chaffeensis polymerase chain reaction (PCR) was positive, and the antibiotic regimen was de-escalated to only doxycycline with complete resolution of his symptoms and progressive improvement in previously abnormal biochemical indices.